LEARNING IMPLEMENTATION PLAN IN THE COURSE OF LEARNING SYSTEM PLANNING STRATEGIES TO REALIZE PEDAGOGICAL COMPETENCIES OF EDUCATION STUDENTS - Abdul Aziz Mubarok; Fauzan Ramdhani; Muhammad Azzam; Rakhmad Agung Hidayatullah; Budi Harjo; Warsito (STMIK Indonesia Banda Aceh, 2026)
Instructional System Planning is a foundational course for pre-service teachers to build professional pedagogical competence. One of the crucial outcomes of this course is the ability to develop an adaptive, systematic, and student-centered Lesson Plan (RPP). This article discusses the restructuring and implementation strategies of RPP development in the Instructional System Planning course to meet modern curriculum challenges. Using a descriptive qualitative approach, this article analyzes how technology integration, authentic assessment, and differentiated learning are formulated into RPP components by students. The review indicates that a strong theoretical mastery of instructional system design (such as the ADDIE or Dick and Carey models) is directly proportional to the quality of the generated lesson plans. This article recommends peer-feedback-based mentoring models and real-case studies in schools to enhance students' practical skills in designing effective and meaningful learning.